2021
DOI: 10.1111/ggi.14253
|View full text |Cite
|
Sign up to set email alerts
|

Associations of neighborhood built and social environments with frailty among mid‐to‐older aged Australian adults

Abstract: Aim: Neighborhood environmental attributes are associated with physical activity and health status. We examined cross-sectional associations of built and social environmental attributes with frailty among community-dwelling mid-to-older aged adults in Australia.Methods: Data from 3419 adults aged 50-74 years living in 200 neighborhoods in Brisbane, Australia, were used. Frailty status was assessed by a frailty index comprising 32 items. The built environment attributes examined were residential density, street… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recently, similar associations between built environmental attributes and frailty have been demonstrated in cross-sectional 34 , 35) and longitudinal studies 36 , 37) . Walking-friendly neighborhoods protect against frailty by promoting everyday physical activity; however, the findings warrant further investigation as a result of being inconsistent 38) .…”
Section: Application Of An Ecological Model For Frailty Preventionmentioning
confidence: 89%
“…Recently, similar associations between built environmental attributes and frailty have been demonstrated in cross-sectional 34 , 35) and longitudinal studies 36 , 37) . Walking-friendly neighborhoods protect against frailty by promoting everyday physical activity; however, the findings warrant further investigation as a result of being inconsistent 38) .…”
Section: Application Of An Ecological Model For Frailty Preventionmentioning
confidence: 89%
“…Studies on children and adolescents often include the education level of parents as a controlling factor instead of the grade level of the participants, and there is generally no need to control marital status [31][32][33][34]. Some studies from Australia used the Index of Relative Socio-Economic Advantage and Disadvantage to control social economic status as this index is readily available and widely used in Australia [35][36][37].…”
Section: Role Of Social Demographic Variablesmentioning
confidence: 99%
“…It is a characteristic of social life, including interpersonal trust, norms of reciprocity, mutual aid, and social involvement [19][20][21]. Studies have found that both community-level SC and individual-level SC are negatively associated with the risk of frailty [22,23]. Living in a community with rich civic participation, such as engagement in social activities, was associated with a lower risk of frailty onset among older adults (OR = 0.94) [23].…”
Section: Introductionmentioning
confidence: 99%